As práticas de ensino da escrita de professores dos anos iniciais do ensino fundamental no contexto heterogêneo da sala de aula - Pinto, Débora Rocha Matos (2025)
This dissertation aimed to investigate the writing instruction practices implemented by teachers in the early years of elementary education with in the heterogeneous classroom context of two public schools in Fortaleza, Brazil. The study focused on the teaching strategies, proposed activities, and assessment tools used by three third-grade teachers to address the diverse needs of their students. The theoretical framework drew on the contributions of Morais (2012), Zabala (2014), Franco (2016), and Leal and Pessoa (2023), emphasizing pedagogical practices, heterogeneity, and written language. An exploratory qualitative approach was adopted, with data collected through classroom observations, lesson plan analysis, and individual interviews with the participating teachers. The data were organized and analyzed using Discursive Textual Analysis (DTA). Findings revealed significant variations in how teachers addressed classroom heterogeneity, both in the irinteractions with students and in their instructional discourse. The study also identified challenges in meeting the specific needs of students, particularly those with diagnosed conditions, and a lack of clear objectives in using assessment tools to support students9 writing development. The research high lights the need for on going professional development, whether in initial or continuing teacher training, focusing not only on theoretical knowledge but also on practical classroom strategies. The study underscores the importance of creating opportunities for dialogue and reflection on classroom challenges, promoting teaching practices that address the diverse individual and collective learning needs of all students, thereby fostering a more inclusive educational environment.